Structure et propriétés chimiques de la «base méthylène» dérivée du 2-méthyl benzothiazole - G. Larive; R. Dennilauler (CHIMIA)
Depending on the procedures used, the quaternary salts of 2-alkyl benzothiazole are likely to lead to acetylated amino thiophenols by hydrolytic opening of the ring, or to 2-alkylidene bases by loss of the ion and a proton attached to the alpha carbon adjacent to the nitrogen atom. Besides, these bases can be obtained by direct ring-closure, starting from substituted amino thiophenols. The molecular structure attributed up to now to the methylene base for explaining the anomaly of its molecular weight is probably erroneous. By physical and chemical methods, it was established that it could not correspond to that, currently admitted, of the cyclobutane dimer. A dissymmetrical structure enables to account for the observed chemical properties : addition on the double link, reactivity of methinic hydrogen, opening of the benzothiazoline ring. It enables also to interpret the reactions of dye formation, notably of those belonging to the mesosubstituted merocyanines and trimethyl cyanines, which bad not been explained up to now.